2020
DOI: 10.1136/bmjgh-2019-002173
|View full text |Cite
|
Sign up to set email alerts
|

The impact of gender equity in agriculture on nutritional status, diets, and household food security: a mixed-methods systematic review

Abstract: IntroductionUndernutrition rates remain high in rural, low-income settings, where large, gender-based inequities persist. We hypothesised that increasing gender equity in agriculture could improve nutrition.MethodsWe conducted a systematic review to assess the associations between gender-based inequities (in income, land, livestock, and workloads) and nutrition, diets and food security outcomes in agricultural contexts of low-income and middle-income countries. Between 9 March and 7 August 2018, we searched 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 46 publications
1
23
0
1
Order By: Relevance
“…It is estimated that reducing food loss and waste in low-and middle-income countries (LMICs) by 10% could reduce fruit and vegetable prices by 14% (10). Reducing loss and waste thus has the potential to reduce hunger and undernutrition (12) while improving the environmental sustainability of the food system (11). The importance of addressing food loss and waste has been recognised in SDG 12, which aims to ensure sustainable consumption and production patterns-including by halving the level of food waste (11).…”
Section: Background and Objectivementioning
confidence: 99%
See 1 more Smart Citation
“…It is estimated that reducing food loss and waste in low-and middle-income countries (LMICs) by 10% could reduce fruit and vegetable prices by 14% (10). Reducing loss and waste thus has the potential to reduce hunger and undernutrition (12) while improving the environmental sustainability of the food system (11). The importance of addressing food loss and waste has been recognised in SDG 12, which aims to ensure sustainable consumption and production patterns-including by halving the level of food waste (11).…”
Section: Background and Objectivementioning
confidence: 99%
“…Gender equality also underpins the achievement of multiple other SDGs-including SDG 2, as women's empowerment and gender equity are key determinants of access to nutritious food and productive resources. With some heterogeneity (12), there is generally a positive association between women's empowerment and their own nutrition and food security and that of their young children (13)(14)(15), with studies linking maternal decision-making (16)(17)(18)(19), autonomy (20,21), and empowerment in agricultural production (22) to indicators of better child or women's nutrition. At present, however, women and girls are disproportionately denied access to education and healthcare, suffer from violence and discrimination, lack access to decent work, and face gender wage gaps-as well as being under-represented in political decision-making (11).…”
Section: Background and Objectivementioning
confidence: 99%
“…Given their low status in society, empowering women is, of course, intrinsically valuable. In addition, some studies have documented linkages with other development goals, such as eliminating poverty, reducing hunger and malnutrition, and achieving good health and well-being for women and their families ( Cunningham et al, 2015 , Malapit et al, 201a , Malapit et al, 2015 , Ruel et al, 2018 , Sraboni et al, 2014 ), though the broader evidence base for low and middle-income countries is mixed ( Harris-Fry et al, 2020 ), and certain time-intensive interventions could have unintended consequences by competing with caregiving, rest or domestic chores like food preparation in certain contexts ( Carlson et al, 2015 , Johnston et al, 2015 , Komatsu et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Women farmers from historically marginalized social groups – Scheduled Castes (SCs) and Scheduled Tribes (STs) – are doubly constrained, as the female and caste disadvantages reinforce each other: a study on gender and agriculture extension in India ( World Bank and IFPRI, 2010 ) found that villages represented by female gram panchayat members from scheduled castes received significantly fewer resources, such as agricultural extension services, than others. These gender-based inequities are, of course, not limited to India, with women in several contexts having lower asset ownership, lower labor force participation and greater work-related burdens ( Harris-Fry et al, 2020 , Ruel et al, 2018 , Doss et al, 2015 , Palacios-López and López, 2015 ). These inequities often serve to limit the ability of agricultural interventions to bolster household incomes and food security and ensure equitable access to nutritious diets ( Harris-Fry et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation